Emerging perovskite materials for high density data storage and artificial synapses. Issue 7 (31st January 2018) - Wang, Yan; Lv, Ziyu; Zhou, Li; Chen, Xiaoli; Chen, Jinrui; Zhou, Ye; Roy, V. A. L.; Han, Su-Ting
Abstract : This review summarizes the recent progress in the development of perovskite materials for non-volatile memories and artificial synapses. Abstract : Since the discovery of perovskite materials with the general chemical formula ABX3 in 1839, research on perovskite materials has drawn exponentially greater attention, owing to their flexible properties, including their ferroelectric, piezoelectric, and dielectric, as well as resistive switching, properties. Perovskite materials have high potential for developing nonvolatile high-density data storage devices. In this review, we summarized the current development of the application of perovskites in nonvolatile memories with an emphasis on the resistive switching properties. The unique advances of perovskite materials are introduced, followed by an assortment of the characterisations of their compositions and crystal structures. The insight into perovskite materials in artificial synapses has also concluded with predictable opportunities and challenges in this promising field.